Salt-leached microporous membranes for lithium batteries - ÇAKMAKÇI, EMRAH (SPRINGER HEIDELBERG, 2015)
Poly(vinylidene fluoride) (PVDF)/sodium hydrogen carbonate (NaHCO3)-based microporous polymer membranes were prepared by salt leaching. In this study, lithium-trifluoromethane sulfonate (LiCF3SO3) was used by dissolving it in solvents like propylene carbonate (PC), dimethyl carbonate (DMC), and diethylene carbonate (DEC). Microporous polymer electrolytes (MPE) were obtained from their porous polymer membranes when immersed in 0.1 M LiCF3SO3 in a mixture of PC/DMC/DEC (2:2:1) electrolyte solution. The membranes were characterized by electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV), chronopotentiometry (CP), chronocoulometry (CC), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FT-IR). The electrochemical stability window of the membrane has been evaluated with LSV using the triple electrode system. Ac conductivities of the Li salt containing membranes were found to be 1.34 x 10(-5) S cm(-1) (GPE100) and 2.69 x 10(-6) S cm(-1) (GPE25).
Keywords: Lithium batteries; Polymer electrolytes; Electrochemical characterizations; GEL POLYMER ELECTROLYTES; HOLLOW-FIBER MEMBRANES; IONIC-CONDUCTIVITY; POLY(VINYLIDENE FLUORIDE); CURRENT-RANGE; MICROFILTRATION; DISTILLATION; PERFORMANCE; PARTICLES; REMOVAL